Green and open space of low cost housing area for residents’ well-being - Mansor, Mazlina; Shaiful Yazan, Siti Sarah (IIUM Press, International Islamic University Malaysia, 2017)
The paper is about the importance of green and open space of low cost housing for residents’ well-being. The green and open space is any piece of land that has no building or large structure and its public networking. Green and open space includes green spaces that have trees, shrubs, ground cover and other types of vegetation. This study is focusing more on low cost housing area that have low income wage earners to afford the house or other factors that might influence them to live there. Although the place it at low cost housing area they also need good quality of green and open space for their well-being and needs. The main issues that have been occurred there is lacking of space or limited space of green and open space and the lack of maintenance of green and open spaces due to income constraints that also affect their mental, physical and social well-being. The aim of the research is 1) to of green and open space and the utilization of space. 2) To identify good characteristic of the good green and open space for residential area. 3) To examine the utilization of green and open space for residential area. The method used in this paper is qualitative research which include observation, behavioural mapping and semi-structured interview with the residents. The findings show that the factors that influence the utilization of green and open space is safety, maintenance issues, size of the space and others. As a conclusion, the study is very significant to green and open space at low cost housing area as it will affect their physical, mental and social well-being.